Pengaruh Pelatihan Kerja dan Pengembangan Karyawan terhadap Kinerja Karyawan Perusahaan PT Baramulti Suksessarana Tbk - Pratama, Arya Saputra; Tricahyadinata, Irsan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of job training and employee development on employee performance at PT Baramulti Suksessarana Tbk. The research employed a quantitative descriptive approach with a population of all company employees totaling 129 people, making the entire population the research sample (census). Data were collected through questionnaires, interviews, literature studies, and documentation, then analyzed using multicollinearity tests, heteroscedasticity tests, normality tests, linear regression analysis, and hypothesis testing using SPSS 23. The results showed that job training and employee development have a positive and significant effect on employee performance, both partially and simultaneously. Based on the coefficient of determination test, the Adjusted R Square value of 0.989 indicates that training and human resource development together contribute 98.9% to employee performance, while the remaining 1.1% is influenced by other factors outside the study. These findings indicate that structured training and sustainable HR development programs have a strategic role in improving employee productivity, professionalism, motivation, and commitment to the company.